Produção da cana-de-açúcar nos municípios de Abaetetuba e Ulianópolis: aspectos climáticos, socioeconômicos e ambientais - VADO ESPINOZA, Julio Cesar (Universidade Federal do Pará, 2019)
In the last decade, the global increase in demand for sugar for food production and renewable energy sources has impacted the production chain and pressing areas with agricultural potential for sugarcane plantation. The Brazilian government through the Ministry of Agriculture Livestock and Supply developed the Agro-Ecological Zoning of Sugar Cane - ZAE (EMBRAPA, 2009) for the production of ethanol and sugar, excluding among other areas the state of Para for been located in the Amazon Biome. Coupled to this context there is the controversy of whether monoculture which requires deforestation practices, which also derive impacts on the atmosphere, water and soil. Before the contrast to produce and protect the environment is relevant deepening of scientific studies for technical support and justification of alternatives for deployment or expansion of cultivation associated with the mapping of areas already consolidated. This study aimed to analyze the production of sugar cane in the city of Abaetetuba and Ulianópolis, taking into account climatic aspects; socioeconomic and environmental. For climate aspects were used (for both municipalities) climatological data provided by INMET a period of thirty years (1984-2013). The results showed that both municipalities have climatic suitability for the cultivation of sugar cane, with the proviso that for the city of Ulianópolis this crop is dependent on irrigation, which increases production costs and causes increased pressure on groundwater. As refer to socioeconomic and environmental aspects were used different methods for the studied municipalities. For the city of Abaetetuba, the socioeconomic aspects were evaluated in light of the situation on the time of cultivation of height in this city (1970). The results showed that activity represented an important vector to generate employment and income for the local population. Environmentally, the assessed indicators showed low vulnerability to contaminants derived from sugarcane cultivation, which can be explained by the intrinsic characteristics of the aquifer and soil properties in the area. As for the land use, the results showed the existence of degraded areas for the year 2012 related to livestock activity mostly. To the municipality of Ulianópolis was applied to Barometer tool of sustainability, defining sustainable development as that which meets the needs of the present without compromising the ability of future generations to meet their own needs (WCED, 1987). It was found that this city is located in an intermediate range of sustainability, and the increased vulnerability indicators deforestation, exploitation of groundwater and hotspots per km2. Although this study has proposed a number of environmental and socio-economic indicators of relevance, further research should be carried out, given the importance of sugar cane for the development of alternative energy in the region. It is also worth mentioning that from the perspective of the institutional environment (credit, regulatory, environmental, etc.) guided by ZAE, new sugarcane enterprises could be encouraged in degraded areas in the Amazon Biome.